Neuromelanin Locus Coeruleus MRI Contrast in Migraine With Aura. Issue 4 (17th February 2020) - Gollion, Cédric; Arribarat, Germain; Ruidavets, Jean‐Bernard; Fabre, Nelly; Barège, Michèle; Bonneville, Fabrice; Larrue, Vincent; Peran, Patrice
Abstract : Introduction: The locus coeruleus (LC) is one of the brainstem nuclei that may be activated during migraine attack. As LC contains neuromelanin, a by‐product of norepinephrine synthesis, it can be delineated in vivo using neuromelanin sensitive magnetic resonance imaging (MRI). The neuromelanin content in LC has been suggested to reflect previous LC activation. We investigated LC MRI contrast in patients with migraine with aura (MWA) and its correlation with migraine features. Methods: This matched cohort study compared 23 MWA patients aged 30‐55 and without comorbidity, to 23 sex‐ and age‐matched healthy controls. The study was conducted in a University Hospital. LC contrast was measured with T1 neuromelanin‐sensitive‐weighted 3T MRI. Voxels were manually selected by 2 independent researchers and comparison was made twice using intersection and union of the voxels selected by the 2 observers. Results: No difference was found in neuromelanin LC contrast between MWA patients and controls with both the INTER method (0.224 ± 0.042 vs 0.228 ± 0.048; difference: 0.0001 (95%CI: −0.032 to 0.026), P  = .799) and UNION method (0.218 ± 0.043 vs 0.222 ± 0.047; difference: −0.0012 (95%CI: −0.031 to 0.026), P  = .775). Global LC volume was also similar between the 2 groups with INTER method (15.087 ± 3.965 vs 13.739 ± 3.583; difference: 2 (95%CI: −1 to 4), P  = .233) and UNION method (17.522 ± 4.440 vs 16.087 ± 4.274; difference: 1 (95%CI: −2 to 4), P  = .270). Moreover, no correlations were found between neuromelanin LC contrast and migraine features (duration of migraine and frequency of attacks). Conclusion: These negative findings do not support the use of neuromelanin LC contrast as a biomarker of MA.